2014
DOI: 10.1177/0013916514525038
|View full text |Cite
|
Sign up to set email alerts
|

Home, Car Use, and Vacation

Abstract: Strategies to promote environmentally friendly behavior among consumers require an understanding of how such behaviors are interrelated. We examined 29 different environmentally significant behaviors, using data from surveys in Germany (n = 967) and in Norway (n = 880). A priori models derived from previous research assuming either environmental behavior as a single factor or as organized by behavioral sectors, degrees of constraint, or frequencies of occurrence did not fit the data. In contrast, a model devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…1 The Rasch model makes use of diverse item or behavior difficulties (i.e., item order) to measure interindividual differences (Rasch, 1960(Rasch, /1980. Note that this difficulty notion within the Rasch model differs from another one that is grounded in subjective or perceived difficulty (see Bratt et al, 2015). Employing Rasch scales, Kaiser and colleagues (e.g., Kaiser & Wilson, 2000;Scheuthle, Carabias-Hütter, & Kaiser, 2005) have found that self-reports of environmentally protective behaviors from different domains can be aggregated to form unidimensional measures within different sociocultural contexts.…”
Section: Dimensionality and Stability Of Behavioral Measures Of Ecolomentioning
confidence: 99%
See 2 more Smart Citations
“…1 The Rasch model makes use of diverse item or behavior difficulties (i.e., item order) to measure interindividual differences (Rasch, 1960(Rasch, /1980. Note that this difficulty notion within the Rasch model differs from another one that is grounded in subjective or perceived difficulty (see Bratt et al, 2015). Employing Rasch scales, Kaiser and colleagues (e.g., Kaiser & Wilson, 2000;Scheuthle, Carabias-Hütter, & Kaiser, 2005) have found that self-reports of environmentally protective behaviors from different domains can be aggregated to form unidimensional measures within different sociocultural contexts.…”
Section: Dimensionality and Stability Of Behavioral Measures Of Ecolomentioning
confidence: 99%
“…One-dimensional measures, such as the GEB, assume that an individual’s behavioral lifestyle reflects a generic intention to protect the environment. In contrast, multidimensional measures (e.g., Bratt, Stern, Matthies, & Nenseth, 2015; Leonard-Barton, 1981; Scott & Willits, 1994; Stragier, Hauttekeete, De Marez, & Brondeel, 2012) are thought to reflect different subjective goals or intentions (Stern, 2000b). Bratt and colleagues (2015), for example, suggested that home-based activities, air travel, and car use represent three distinctly different domains of environmentally protective behavior.…”
Section: Dimensionality and Stability Of Behavioral Measures Of Ecolomentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless focusing on specific behaviours in isolation continues to be the standard approach to promoting energy reduction and other pro-environmental behaviour [8,9]. A concentration on single behaviours may in fact be inappropriate given evidence which suggests that groups of pro-environmental behaviours co-vary [10][11][12]. Indeed there is some evidence that concentrating on a single behaviour could be counter-productive as it can lead individuals to focus their pro-environmental intentions on that particular behaviour rather than on behaviours that may have greater environmental impact [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Given the limited success of behaviour change initiatives in reducing energy use or promoting increases in other pro-environmental behaviour, there is an urgent need to understand how such behaviour can be encouraged. Stern [13] and others [12,16,17] have pointed out that pro-environmental behaviour is multidimensional, with different determinants for different behaviours. The difficulty with commonly used behaviour change models such as the Theory of Planned Behaviour [18] and the Value-Belief-Norm Theory [13] is that they are not generally useful for predicting multiple behaviours [5].…”
Section: Introductionmentioning
confidence: 99%